Fabrication of noble metal modified titania photoanode for higher efficiency dye-sensitized solar cells / Lim Su Pei - Lim, Su Pei (2015)

(untitled)
The dye-sensitized solar cells (DSSCs), taken as a new generation or potential alternative for the traditional silicon and thin films solar panels, is an efficient and economical way to directly convert solar energy to electricity. The significant development of the DSSC technology has demonstrated its capability for future renewable solar electricity generation. One of the major challenges of this technology is that the efficiency is still less than half that of a single-crystal silicon cell. If the efficiency of DSSCs can be improved, these devices could significantly reduce the cost compared to the first and second generation photovoltaic devices. To address this problem, designing a novel photoanode with an efficient transport pathway from the photoinjected carriers to the current collector seems to be an attractive alternative to enhance the performance of DSSCs. Herein, the thesis reported on the synthesis of noble metal nanoparticles modified photoanode and investigation of the relationship between the photoanode and the device performance. This research work was divided into four stages. The initial study focused on the synthesis of silver-titanium dioxide (Ag@TiO2) nanocomposite materials. A single-step chemical reduction has been employed to synthesize binary nanocomposite films of Ag@TiO2. An ultra-small Ag nanoparticle with a particle size range of 2-4 nm was uniformly distributed on the TiO2 surface. The incorporation of Ag on the TiO2 surface significantly influenced the optical properties in the region of 400–500 nm because of the surface plasmon resonance effect. The DSSC assembled with the Ag@TiO2-modified photoanode demonstrated a better solar-to-electrical energy conversion efficiency, η (4.86 %) than that of bare TiO2 (2.57 %) due to the surface plasmon resonance effect. The SPR effect not only increase the number of excited electron being transferred to the current collector but also assist in trapping the light and near-field coupled with the dye molecules, hence improve the efficiency. The second part of the work was to improve the absorption to the visible iv region on the TiO2 material by the integration of non-metal into TiO2, specifically nitrogen (N), to improve the light absorption. Nitrogen has received attention due to the narrowing of band gap and shift to the visible region. Increase η (up to 8.15 %) was observed through the integration of Ag and N into TiO2. The third stage of the work was to investigate the effect of co-deposition of sulphur (S) and N on TiO2 for the photovoltaic properties enhancement. The DSSC fabricated with N,S-TiO2-Ag showed an enhanced η of 8.22 % when compared to that of the unmodified TiO2. The approximate 3-fold enhancement was contributed by the synergetic effects among the elements that modified the TiO2, resulting in surface plasmon effect, reduction of band gap and effective charge transfer. The final studies sought to focus on bimetal gold (Au) and Ag modified TiO2, which aimed to further enhance the overall efficiency by utilizing the plasmon resonance effect of Ag and Au. Finally, the greatly improved overall efficiency of 9.54% was attributed to the optimum Ag/Au ratio and uniformly dispersed Ag/Au nanoparticles on the TiO2 surface.